Persepsi Mahasiswa Terhadap Budaya dan Perilaku Sosial Pada Masyarakat Yogyakarta - Muhammad Zainal Fanani; Rifa Yasmin Nailufar; Vinka Warrowa (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
This study aims to determine student perceptions of the culture and social behavior of the people of Yogyakarta. The subjects in this study were active students aged 18-23 years. This study used qualitative research methods and data collection techniques used in this study were semi-structured interviews. The result of this research is that the cultural environment has a great influence on the formation of oneself and one's behavior. In Yogyakarta society itself, the presence of a culture such as gotong royong can provide positive reinforcement and influence on social behavior to the people around them.Keywords: Perception, Culture, Social Behavior